The influence of phase angle, strain range and peak cycle temperature on the TMF crack initiation behaviour and damage mechanisms of the nickel-based superalloy, RR1000. (May 2017) - Jones, Jonathan; Whittaker, Mark; Lancaster, Robert; Williams, Stephen
Highlights: Thermo-mechanical fatigue testing of a nickel superalloy across multiple strain ranges. Six diverse phase angles between 0° and −180° and various peak cycle temperatures are used. Evolution of mean stresses and the influence of oxidation upon failure mechanisms are assessed. Relationships between test life, phase angle and mean stresses are realised. Abstract: Thermo-mechanical fatigue (TMF) tests including 0°, 90°, −90°, 45° −135° and −180°, phasing (φ) between mechanical loading and temperature were undertaken on a polycrystalline nickel-based superalloy, RR1000. Mechanical loading was employed through strain control whilst 300–700 °C and 300–750 °C thermal cycles were achieved with induction heating and forced air cooling. Mechanical strain ranges from 0.7 to 1.4% were employed. Results show that, for the strain ranges tested, TMF life is significantly affected by the employed phase angle. Furthermore the strain range and peak cycle temperature used has a substantial influence on the significance of dominant damage mechanisms, and resultant life. Various metallographic examination techniques have outlined that the dominant damage mechanisms are creep deformation at higher temperatures and early cracking of oxide layers at lower temperatures.